TEACHERS' DIFFICULTIES IN LESSON PLANNING - Farid, Miftah (2014)
This study investigated the teachers' preparation in developing lesson plans, in terms of formulating objectives, developing materials and media, plotting the teaching procedures and conducting students' evaluation; also pictured their consideration and difficulties in planning lessons for their classes. As the study employed qualitative data analysis, the data were collected through document analysis on lesson plans, also conducting interview with the teachers. The data then were analyzed using Miles and Huberman's (1994) interactive model. The findings showed that in developing the lesson plans the teachers applied the systematic planning proposed by Reiser and Dick (1996), in which they started with analyzing the syllabus, followed by formulating objectives and indicators, selecting learning materials, and designing learning activities and assessment procedure. However, the interview result showed that the teachers dealt with some problems during the process, such as formulating indicators, selecting materials, determining learning activities, selecting media and developing assessment procedure. Based on the findings in this study, it is recommended that the teachers improve their competences in lesson planning.